Azithromycin and ceftriaxone in uncomplicated typhoid fever in paediatric patients: a prospective, comparative and randomized open labelled trail - Rao, K. Narayan; Pratyusha, R.; Acharya, Anand (International Journal of Contemporary Pediatrics, 2020)
Background: Typhoid fever is a life-threatening infection caused by the bacterium Salmonella typhi. There are limited options for treatment of typhoid fever in children. Carbapenems and azithromycin are two drugs which is available for treatment of infection caused by extensively drug-resistant (XDR) strain of Salmonella typhi. Methods: This is a prospective, comparative, randomized open labelled trail conducted in the department of paediatrics Konaseema institute of medical science, Amalapuram, Andhra Pradesh. Blood sample was obtained from each patient before start of treatment for determination of complete blood count and differential count at baseline. Everyday each patient was evaluated clinically. Results: The mean duration of fever after start of treatment was 4.41.46 days in group treated by azithromycin and 3.95+1.02 days in group treated by ceftriaxone which is little early without statistical significance. Conclusions: From present study we can conclude that azithromycin 20 mg/kg/day is as effective as ceftriaxone 75 mg/kg/day for the treatment of typhoid fever in children. Clinical and microbiological cure was comparable in both groups. There was no incidence of relapse of fever in azithromycin treatment group. Diarrhoea was common in patients treated with ceftriaxone and nausea and vomiting was more common in patient treated with azithromycin.